Estimation of low order odd current harmonics in short chorded induction motors using Artificial Neural Network - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2008)
In this paper, Artificial Neural Network (ANN) technique has been used for the estimation of low order odd current harmonics mainly from input and output measurements of five different chorded induction motors. A sinusoidal pulse-width modulation (SPWM) inverter feeding five different chorded three-phase induction motors were tested up to first thirty harmonic voltage component at different loads. The results show that the artificial neural network model produces reliable estimates of low order odd current harmonics.
Keywords: Artificial Neural Network; total harmonic distortion; harmonic estimation; induction motors